2020
DOI: 10.29133/yyutbd.628921
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Farmyard Manure and Green Manure Applications on Some Soil Physical Properties

Abstract: In this research was carried out to determine the effects of farmyard manure and green manure applications on some soil physical properties in a three yearly organic vegetable cultivation field. The effects of control (C), farmyard manure (FYM) (35 t ha-1) and green manure (GM) applications on some soil physical properties (soil water characteristics (0.001, 0.1, 0.33, 1, 5, 10 and 15 bars), available water content, porosity and bulk density) were investigated in 0-10 and 10-20 cm soil depths for two years. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In their study on the effects of organic material applications on water retention and water-entry value, Liyanage and Leelamanie (2016) reported that the soil water content significantly and linearly increased with increasing organic material content. Again, Müjdeci et al (2020) reported that stable manure and green manure applications increased volumetric water content at all retention pressure. Barzegar et al (2002) stated that organic material applications increased the water content held at levels below 100 kPa.…”
Section: Introductionmentioning
confidence: 98%
“…In their study on the effects of organic material applications on water retention and water-entry value, Liyanage and Leelamanie (2016) reported that the soil water content significantly and linearly increased with increasing organic material content. Again, Müjdeci et al (2020) reported that stable manure and green manure applications increased volumetric water content at all retention pressure. Barzegar et al (2002) stated that organic material applications increased the water content held at levels below 100 kPa.…”
Section: Introductionmentioning
confidence: 98%